Clinical epidemiology the essentials - Fletcher, Grant S.; Preceded by (work): Fletcher, Robert H. (Philadelphia Wolters Kluwer, 2021)
"This book is for clinicians-physicians, nurses, physicians' assistants, psychologists, veterinarians, and others who care for patients-who want to understand for themselves the strength of the information base for their clinical decisions"-- Provided by publisher.
Frequency -- Abnormality -- Diagnosis -- Risk: Basic Principles -- Risk: Exposure to Disease -- Risk: From Disease to Exposure -- Prognosis -- Treatment -- Prevention -- Chance -- Cause -- Summarizing the Evidence -- Knowledge Management
Preceded by Clinical epidemiology / Robert H. Fletcher, Suzanne W. Fletcher, Grant S. Fletcher. 5th ed. c2014.
Includes bibliographical references and index.
Keywords: Epidemiologic Methods